Analysis of Mn nodules from cruise GH72-2 - Takeda, Hideo; Maruyama, Shuji; Yamakado, Norio; Inoue, Eiji; Iso, Miyoji; Matsumoto, Sakae; Suzuki, Taisuke; Usami, Takeshi; Tsurusaki, Katsuya; Handa, Keiji; Matsumoto, Eiji; Yuasa, Makoto (Supplement to: Takeda, H et al. (1975): Manganese nodules and their prospecting around the Mariana Basin in the Northwestern Pacific. Bulletin of the Geological Society of Japan, 26(11), 1-445, https://www.gsj.jp/en/publications/bull-gsj/geppou26-11.html, 1975)
The GH72-2 shipborne survey was carried out in the northwest Pacific during 31 days under the 'Basic investigations for exploration of deep sea mineral resources' program. The sediments encountered could be classified as follows: 1) Most of the brown clays occur on the abyssal plain of the basins at depth over 4500m. 2) Calcareous oozes are predominant at the top, slope and foot of seamounts and guyots. 3) Terrigeneous sediments are distributed near islands. The concentrated zone of ferromanganese nodules was located in the Magellan seamounts area. However, the metal contents in Mn, Cu, Ni and Co for these nodules are relatively poor, and these ferromanganese deposits occur at a depth over 5000m. It is interesting to note that the shape of the nodules is sometimes nearly spherical, and that the chemical composition of the nodules is characterized by the low ratio Mn/Fe and Co/Ni.